HUBUNGAN LINGKUNGAN SOSIAL DAN SPIRITUAL DENGAN PENYALAHGUNAAN NARKOBA PADA PENGHUNI LPKA (LEMBAGA PEMBINAAN KHUSUS ANAK) PROVINSI SUMATERA BARAT TAHUN 2018 - Lilisa Murni; Rany Desmawati (LPPM UNIVERSITAS PERINTIS INDONESIA, 2018)
Cases of drug abuse in West Sumatra became very important to note because it has increased as much as 635 cases year 2015 be 824 cases in the year 2016. The purpose of this research is to know the social environment and spiritual relationship with drug abuse on residents of West Sumatra LPKA year 2018. This research was conducted on 21-25 February 2018 with design research using descriptive analytic approach using cross sectional. The number of samples in the study as many as 37 people with techniques of sampling respondents total sampling. This research instrument using a detailed questionnaire. The results of this research show that the social environment supports as much of 48.6%, which has a less good spiritual as much as 51.4% and 64.9% of heavy drug abuse. The research results obtained there is the relationship between the environment and drug abuse sosail (ρ = 0.008 and OR = 11,000) and there is a spiritual connection with drug abuse (ρ = 0.001 and OR = 29.143). It can be concluded that there is a social and spiritual environment relationship with drug abuse on residents of West Sumatra LPKA year 2018 and recommended to all residents of West Sumatra Province LPKA in order to further improve the spritualitas and stay away from negative social environment and also for the next researcher can use other variables such as economic factors and the intelligentsia against drug abuse.